2023
DOI: 10.3389/fneur.2023.1167957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 weeks of Tai Chi on neuromuscular responses and postural control in elderly patients with sarcopenia: a randomized controlled trial

Abstract: ObjectiveTo explore the effect of 12 weeks of Tai Chi on neuromuscular responses and postural control in elderly patients with sarcopenia.MethodsOne hundred and twenty-four elderly patients with sarcopenia from ZheJiang Hospital and surrounding communities were selected, however, 64 were later disqualified. Sixty elderly patients with sarcopenia were randomly assigned to the Tai Chi group (n = 30) and the control group (n = 30). Both groups received 45-min health education sessions once every 2 weeks for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Tai Chi may improve dynamic postural control during the initial phase of GI in older adults by altering the movement characteristics of the CoP. Another study revealed that a 12-week Tai Chi exercise can improve posture control on unstable platforms and reduce the risk of falls in older individuals with sarcopenia ( Huang et al, 2023 ). However, a previous research that compared the minimum postural sway ability of older adults suggested that a 15-week Tai Chi intervention did not improve measures of platform postural stability ( Wolf et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tai Chi may improve dynamic postural control during the initial phase of GI in older adults by altering the movement characteristics of the CoP. Another study revealed that a 12-week Tai Chi exercise can improve posture control on unstable platforms and reduce the risk of falls in older individuals with sarcopenia ( Huang et al, 2023 ). However, a previous research that compared the minimum postural sway ability of older adults suggested that a 15-week Tai Chi intervention did not improve measures of platform postural stability ( Wolf et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training improved respiratory muscle strength with concurrent improvement of exercise capacity [ 56 ]. Huang [ 57 ] revealed in their study that a Taichi training program significantly reduced the neuromuscular response time in the rectus femoris, semitendinosus, gastrocnemius, and tibialis anterior muscles of the lower limb in older adults with sarcopenia. Furthermore, dynamic postural control abilities were significantly enhanced.…”
Section: Discussionmentioning
confidence: 99%